Next-Generation Probiotic Therapy to Protect the Intestines From Injury - Ragan, Mecklin V.; Wala, Samantha J.; Goodman, Steven D.; Bailey, Michael T.; Besner, Gail E. (Frontiers in Cellular and Infection Microbiology, 2022)
Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit to the host. Some strains of the probiotic Lactobacillus reuteri (Lr) have both anti-microbial and anti-inflammatory properties that may be exploited for the treatment and prevention of different gastrointestinal diseases, including necrotizing enterocolitis (NEC) and Clostridioides difficile (C. difficile) infection. Our laboratory has developed a new delivery system for Lr in which the probiotic is incubated with biocompatable, semi-permeable, porous dextranomer microspheres (DM) that can be loaded with beneficial and diffusible cargo. Lr can be induced to form a biofilm by incubating the bacteria on the surface of these microspheres, which enhances the efficacy of the probiotic. Loading the DM with sucrose or maltose induces Lr to produce more biofilm, further increasing the efficacy of the probiotic. Using a rat model of NEC, Lr administered in its biofilm state significantly increases animal survival, reduces the incidence of NEC, preserves gut barrier function, and decreases intestinal inflammation. In a murine model of Clostridiodes difficile infection, Lr administered in its biofilm state decreases colitis when administered either before or after C. difficile induction, demonstrating both prophylactic and therapeutic efficacy. There are currently no FDA-approved probiotic preparations for human use. An FDA-approved Phase I clinical trial of Lr in its biofilm state in healthy adults is currently underway. The results of this trial will be used to support a Phase 1 clinical trial in neonates, with the goal of utilizing Lr in its biofilm state to prevent NEC in premature neonates in the future.